Disrupting the dominance of 'linear pathways': how institutional assumptions create 'stuck places' for refugee students' transitions into higher education. Issue 1 (2nd January 2021) - Baker, Sally; Irwin, Evonne
ABSTRACT: Although journeys into and through higher education can be challenging for all learners, students from refugee backgrounds (SfRBs) face particular difficulties due to their culturally and linguistically diverse (CALD) backgrounds, and pre-settlement experiences of instability, insecurity, likely trauma and interrupted education. Drawing on a longitudinal, ethnographic exploration of the educational trajectories of a group adult SfRBs living in a regional Australian city, this article questions how 'traditional' understandings of transition – as linear, ritualised and predictable – can account for the complex lived experiences of SfRBs trying to access and participate in higher education studies in a resettlement context. Working with the anthropological notion of liminality (Turner 1969; Van Gennep 1960) and the notion of 'stuck places' (Lather 1998), we offer a more nuanced understanding of how 'messy' educational transitions are experienced, and how normative notions of what transition 'should be' act to mask these experiences, leaving SfRBs 'stuck' in the liminal space of becoming a student in higher education.